If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) + -1(2 + -1x) = 5(x + -2) + 4 Reorder the terms: 4(-1 + x) + -1(2 + -1x) = 5(x + -2) + 4 (-1 * 4 + x * 4) + -1(2 + -1x) = 5(x + -2) + 4 (-4 + 4x) + -1(2 + -1x) = 5(x + -2) + 4 -4 + 4x + (2 * -1 + -1x * -1) = 5(x + -2) + 4 -4 + 4x + (-2 + 1x) = 5(x + -2) + 4 Reorder the terms: -4 + -2 + 4x + 1x = 5(x + -2) + 4 Combine like terms: -4 + -2 = -6 -6 + 4x + 1x = 5(x + -2) + 4 Combine like terms: 4x + 1x = 5x -6 + 5x = 5(x + -2) + 4 Reorder the terms: -6 + 5x = 5(-2 + x) + 4 -6 + 5x = (-2 * 5 + x * 5) + 4 -6 + 5x = (-10 + 5x) + 4 Reorder the terms: -6 + 5x = -10 + 4 + 5x Combine like terms: -10 + 4 = -6 -6 + 5x = -6 + 5x Add '6' to each side of the equation. -6 + 6 + 5x = -6 + 6 + 5x Combine like terms: -6 + 6 = 0 0 + 5x = -6 + 6 + 5x 5x = -6 + 6 + 5x Combine like terms: -6 + 6 = 0 5x = 0 + 5x 5x = 5x Add '-5x' to each side of the equation. 5x + -5x = 5x + -5x Combine like terms: 5x + -5x = 0 0 = 5x + -5x Combine like terms: 5x + -5x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| -x-4(0)=6 | | -x+2=3x+4x | | -15=3x+6 | | 7/5x+8/3x | | 5x-12x=56 | | 7c-9=9(2c-8)+4c | | B+3.5B=81 | | 8+2t+2=2(t+5) | | 3x-2+x+8=2(3x+7-x-4) | | 2a+1=16 | | 6-x=32 | | 2x*15= | | 5-x+3x=17 | | -3+2x=2x-3 | | 22=a+2d | | 6-5x-x=66 | | -3(0)+2y=9 | | 584=348 | | s-q=p | | -2n=-3n+6 | | -16+x=7 | | 216/18 | | -14n+12=-10n-16 | | 4(c-8)=3(5+c) | | x/5=0 | | -15=6+X | | 0.5(2x-8)=7x+10 | | 18=2x+4x | | 1/2g=31/3 | | x-100/5.3 | | -5=x-(-1) | | t/5-3=7 |